An Effective Method of Analysing Student Performance Using Fuzzy Numbers - A. N. Revathi; A. Karpagam; M. Suguna; null Salahuddin (Advances in Fuzzy Systems)
In the context of rapid scientific and technological advancements, engineering is increasingly becoming a vital career choice. However, students from rural areas often encounter significant challenges in their engineering studies and extracurricular activities, leading to higher dropout rates compared to their urban counterparts. To address this issue, we have developed a mathematical model that utilises fuzzy numbers and Newton’s method to strategically prioritize core engineering activities. This model is designed to account for the unpredictability of student performance and aims to bridge the educational gap between urban and rural students. By focusing on essential activities, our approach seeks to enhance academic outcomes and increase success rates for engineering students across diverse educational settings. This innovative method provides a novel solution to the persistent educational disparities, offering a pathway to more equitable and effective engineering education for all students.